Density of tumor-infiltrating lymphocytes correlates with extent of brain edema and overall survival time in patients with brain metastases. (2nd January 2016) - Berghoff, Anna S; Fuchs, Elisabeth; Ricken, Gerda; Mlecnik, Bernhard; Bindea, Gabriela; Spanberger, Thomas; Hackl, Monika; Widhalm, Georg; Dieckmann, Karin; Prayer, Daniela; Bilocq, Amelie; Heinzl, Harald; et al.
Abstract : The immune microenvironment of the brain differs from that of other organs and the role of tumor-infiltrating lymphocytes (TILs) in brain metastases (BM), one of the most common and devastating complication of cancer, is unclear. We investigated TIL subsets and their prognostic impact in 116 BM specimens using immunohistochemistry for CD3, CD8, CD45RO, FOXP3, PD1 and PD-L1. The Immunoscore was calculated as published previously. Overall, we found TIL infiltration in 115/116 (99.1%) BM specimens. PD-L1 expression was evident in 19/67 (28.4%) BM specimens and showed no correlation with TIL density ( p > 0.05). TIL density was not associated with corticosteroid administration ( p > 0.05). A significant difference in infiltration density according to TIL subtype was present ( p < 0.001; Chi Square); high infiltration was most frequently observed for CD3+ TILs (95/116; 81.9%) and least frequently for PD1+ TILs (18/116; 15.5%; p < 0.001). Highest TIL density was observed in melanoma, followed by renal cell cancer and lung cancer BM (p < 0.001). The density of CD8 + TILs correlated positively with the extent of peritumoral edema seen on pre-operative magnetic resonance imaging ( p = 0.031). The density of CD3+ (15 vs. 6 mo; p = 0.015), CD8 + (15 vs. 11 mo; p = 0.030) and CD45RO+ TILs (18 vs. 8 mo; p = 0.006) showed a positive correlation with favorable median OS times. Immunoscore showed significant correlation with survival prognosis (27 vs. 10 mo; p < 0.001). The prognostic impact of Immunoscore was independent from established prognostic parameters at multivariable analysis (HR 0.612, p < 0.001). In conclusion, our data indicate that dense TILs infiltrates are common in BM and correlate with the amount of peritumoral brain edema and survival prognosis, thus identifying the immune system as potential biomarker for cancer patients with CNS affection. Further studies are needed to substantiate our findings.